Validity of Social Cognition Measures in the Clinical Services for Autism Spectrum Disorder - Pino, Maria Chiara; Masedu, Francesco; Vagnetti, Roberto; Attanasio, Margherita; Di Giovanni, Chiara; Valenti, Marco; Mazza, Monica (Frontiers in Psychology, 2020)
Abstract The current study evaluated three social cognition (SC) tests for their clinical utility in aiding autism diagnosis. To do so, we compared the performance of 86 children with autism spectrum disorder (ASD) and 68 typically-developing (TD) children, all aged from 4 to 10 years old, on three SC tasks (the Social Information Processing Interview [SIPI], the Comic Strip Task [CST] and the children’s version of the Eyes Task) and calculated threshold scores that best differentiated the two groups. While difficulties in these abilities appear to represent the ‘central core’ of ASD, services have largely ignored SC tests when supporting autism diagnoses. Therefore, this study attempted to validate and evaluate the diagnostic potential of these three tasks for children with ASD. To investigate the accuracy of these SC tests, we used the receiver operating characteristic (ROC) curve. As expected, the ASD group performed worse than the TD group on the SIPI and CST, but contrary to our prediction, the groups did not significantly differ on the Eyes Task. Specifically, the overall area under the curve (AUC) for the SIPI was 0.87, with a sensitivity of 73.5% and specificity of 83.9% at the best cut-off point (score range 0–36; best cut-off = 31). The overall AUC for the CST was 0.75, with a sensitivity of 71.1% and specificity of 77.0% at the best cut-off point (score range 0–15; best cut-off = 11). The overall AUC for the Eyes Task was 0.51, with a sensitivity of 50.3% and specificity of 40.2% at the best cut-off point (score range 0–54; best cut-off = 45). In conclusion, the results showed that the SIPI test has good predictive power for classifying children with ASD. It should provide substantial supplementary clinical information and help to consolidate diagnostic procedures based on standard tools. Moreover, the results of the study have substantial implications for clinical practice: the better the knowledge of SC functioning in children with ASD, the more effective the intervention program for rehabilitation.